Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies - William S. Harris (Nature Portfolio, 2021)
Associations between of omega-3 fatty acids and mortality are not clear. Here the authors report that, based on a pooled analysis of 17 prospective cohort studies, higher blood omega-3 fatty acid levels correlate with lower risk of all-cause mortality.